Horizontal Cell Feedback to Cone Photoreceptors in Mammalian Retina: Novel Insights From the GABA-pH Hybrid Model - Barnes, Steven; Grove, James C. R.; McHugh, Cyrus F.; Hirano, Arlene A.; Brecha, Nicholas C. (Frontiers in Cellular Neuroscience, 2020)
How neurons in the eye feed signals back to photoreceptors to optimize sensitivity to patterns of light appears to be mediated by one or more unconventional mechanisms. Via these mechanisms, horizontal cells control photoreceptor synaptic gain and enhance key aspects of temporal and spatial center-surround receptive field antagonism. After the transduction of light energy into an electrical signal in photoreceptors, the next key task in visual processing is the transmission of an optimized signal to the follower neurons in the retina. For this to happen, the release of the excitatory neurotransmitter glutamate from photoreceptors is carefully regulated via horizontal cell feedback, which acts as a thermostat to keep the synaptic transmission in an optimal range during changes to light patterns and intensities. Novel findings of a recently described model that casts a classical neurotransmitter system together with ion transport mechanisms to adjust the alkaline milieu outside the synapse are reviewed. This novel inter-neuronal messaging system carries feedback signals using two separate, but interwoven regulated systems. The complex interplay between these two signaling modalities, creating synaptic modulation-at-a-distance, has obscured it’s being defined. The foundations of our understanding of the feedback mechanism from horizontal cells to photoreceptors have been long established: Horizontal cells have broad receptive fields, suitable for providing surround inhibition, their membrane potential, a function of stimulus intensity and size, regulates inhibition of photoreceptor voltage-gated Ca2+ channels, and strong artificial pH buffering eliminates this action. This review compares and contrasts models of how these foundations are linked, focusing on a recent report in mammals that shows tonic horizontal cell release of GABA activating Cl− and HCO3− permeable GABA autoreceptors. The membrane potential of horizontal cells provides the driving force for GABAR-mediated HCO3− efflux, alkalinizing the cleft when horizontal cells are hyperpolarized by light or adding to their depolarization in darkness and contributing to cleft acidification via NHE-mediated H+ efflux. This model challenges interpretations of earlier studies that were considered to rule out a role for GABA in feedback to cones.